Impact of using solar heat pumps for domestic hot water in Portuguese residential buildings - Monteiro, Joaquim (2016)
In recent years, we have seen an improvement of existing facilities in dwellings in Portugal. Within the heat pumps systems, there is a special type known as direct expansion heat pump assisted by Solar Collector (DX-SAHP). It was calculate the SPF indicator for 30 regions of Portugal. It was analyses the potential of reductions of CO2 and primary energy use for the retrofitting of DHW preparation systems. It was found that the performances of this type of equipment are benefiting from the Portuguese climate conditions, especially in the South and in the Autonomous Regions. Best SPF was obtained for Beja. It was found in all regions of the high potential for reducing CO2 emissions and verifying a potential significant reduction of primary energy consumption.